PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN - Nirmala Putri Sari; Dr. Ismail Razak, M.Si. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
The aim of this study was to analize the effects of product quality and service quality on the customer satisfaction. This study took place in the City of Bekasi and objects in this study are all customer who use the Matrass GM-9000. Primary data was obtained from customers of Matrass GM-9000 in Bekasi City through admission filling of questionnaire by using scale of Likert. The respondent of this study was chosen through accidental sampling method, and data analysis method was simple linear regression and multiple linear regression. The results of this study indicated that product quality and service quality positively and significant influenced the customer satisfaction.